PENGARUH PROFITABILITAS, LIKUIDITAS, DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PUBLIKASI LAPORAN KEUANGAN PERUSAHAAN SEBELUM DAN SAAT PANDEMI COVID-19 - Rismiana, Eka; Suhendro, Saring (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to determine the influence of profitability, liquidity and audit opinion on the timeliness of publication of company financial reports before and during the Covid-19 pandemic. The object of this study is manufacturing companies in the consumer goods industry sector listed on the IDX for 2018-2021. The sample for this study was 43 manufacturing companies in the consumer goods industry sector using a purposive sampling method. Hypothesis testing uses logistic regression testing. The study results show that there is a significant positive influence of the profitability variable with the Return on Assets (ROA) proxy and the D-Years variable on the timeliness of the publication of financial reports before and during the occurrence of Covid-19. Meanwhile, for the liquidity variable with the current ratio proxy and audit opinion, there is no significant positive influence of the profitability variable with the Return on Assets (ROA) proxy and the D-Years variable on the timeliness of the publication of financial reports before and during the occurrence of Covid-19